Pengembangan Bahan Ajar Matematika Berbentuk Leaflet Berbasis Kemampuan Kognitif Siswa Berdasarkan Teori Bruner - widodo winarso; Dede Dewi Yuliyanti (Universitas PGRI Madiun, 2017)
Many students who are less interested in math. Therefore, innovation becomes important so that math learning can be attractively packaged. One of innovation is a development of teaching materials to create teaching materials in the form of the leaflet. The purpose of this study is to develop leaflet teaching materials on the subjects of cube and beam based on student’s cognitive abilities referred Bruner’s theory. Bruner's cognitive stage of the theory that there are three stages enaktif, iconic and symbolic. A research method that used by researcher is research method and development. The model used is the design development according to Sugiyono, consists of problem identification, data collection, preparation of teaching materials, design validation, design revisions, product testing, product revision, utility testing. Aspects of assessment used were the product assessment by experts, cognitive ability tests students based on the theory of Bruner and student response sheet. In the product assessment consist of worthiness content, display, language, and completeness of the component